A Study on Using Hands-on Science Inquiries to Promote the Geology Learning of Preservice Teachers - Ching-San Lai (Seyit Ahmet Kıray, 2015)
This study aims to investigate the geology learning performance of preservice teachers.  A total of 31 sophomores (including 11 preservice teachers) from an educational university in Taiwan participated in this study.  The course arrangements include class teaching and hands-on science inquiry activities.  The study searches both quantitative and qualitative data as the sources for the analyses.  The quantitative data are taken from the results of four specimen identification tests; the respondents are required to take a pre-test before teaching and then practice the explorative hands-on science activities.  Afterwards, the scores of test results are used as the foundation of the analyses.  The qualitative data are the feedback from the preservice teachers in the study.  The research results show the results of the four post-tests are significantly better than those of the four pre-test scores, indicating the preservice teachers' concepts of minerals and rocks significantly improved.  The analysis of the qualitative data also found the preservice teachers demonstrate a good understanding on geology content during geological inquiries.  According to the research results, this study believes the cultivation of and training in hands-on geology inquiries can actually enhance preservice teachers' learning performances in geology.